Prevention and Control of Pulmonary TB Through Socialization, Screening, and Demonstration - Fifi Alviana; Candra Dewi Rahayu (Global Health Science Group, 2020)
Uneducated of society is one of the obstacles in the prevention of TB. One of the interventions to increase public knowledge is health education or socialization about TB disease. The purpose of the activities was to socialize and screen for TB. The method used socialization of health education about tuberculosis, screening TB for participants and demonstration about cough effectively with a total of 450 students from the Faculty of Tarbiah UNSIQ. The results of the activity showed the enthusiasm of the participants in the socialization and demonstration activities. Screening results showed that 412 without symptoms of TB, 23 were symptomatic and refused to be tested for BTA and 15 populations were symptomatic and willing to do a BTA test. Socialization, screening and demonstrations did effectively.